Mediating role of plasma metabolites in the association between plasma proteins and knee osteoarthritis - Haibo Zheng; Ping Zeng; Xianqiu Li; Hao Ni; Longlong Wei; Xueshen Mo; Kun Hou; Xiangbin Rong (Medicine, 2026)
Knee osteoarthritis (KOA) is a prevalent degenerative joint disease with limited treatment options, and the regulatory roles of plasma proteins and metabolites in its pathogenesis remain largely unclear. To explore the causal relationships and correlations among plasma proteins, plasma metabolites, and KOA, we constructed a regulatory network integrating these 3 components. We selected a total of 4907 plasma proteins as exposure variables, 1400 plasma metabolites as mediating variables, and KOA as the outcome variable in this study. We employed inverse variance weighting as the primary analytical approach and performed pleiotropy and heterogeneity tests to guarantee the robustness of the results; additionally, we conducted reverse Mendelian randomization analysis to validate the rationality of the exclusion restriction assumption. Subsequently, we implemented mediation analysis for plasma proteins exhibiting a significant causal association with KOA. Inverse variance weighting analysis identified 2 plasma proteins with significant causal associations with KOA: insulin-like growth factor-binding protein 3 was positively correlated with KOA susceptibility ( β = 0.065, odds ratio = 1.067, P = .004, 95% confidence interval: 1.021–1.115), whereas collagen type XVIII alpha 1 chain was negatively correlated with KOA ( β = −0.111, odds ratio = 0.895, P = .005, 95% confidence interval: 0.830–0.966); no reverse causal relationships were detected for either protein. Mediation effect analysis revealed 20 plasma metabolites with significant mediating associations with KOA; notably, insulin-like growth factor-binding protein 3 could downregulate the levels of N-acetylmethionine and 2-O-methylascorbic acid, thereby promoting the progression of KOA. Collectively, the identified causal associations and mediating effects provide a theoretical foundation and research orientation for the development of KOA therapeutic strategies targeting plasma proteins.